P221 Treatment fidelity in the Gait Rehabilitation in Early Rheumatoid Arthritis Trial (GREAT) feasibility study. (20th April 2020) - Godfrey, Emma; Sekhon, Mandeep; Hendry, Gordon; Foster, Nadine E; Hider, Samantha; van der Leeden, Marike; Mason, Helen; McConnachie, Alex; McInnes, Iain; Patience, Aimie; Sackley, Catherine; Steultjens, Martin; et al.
Abstract: Background: Many people with early rheumatoid arthritis (RA) report foot pain and walking disability. Self-reported walking disability two years post-diagnosis is the main predictor of persistent disability. A psychologically informed gait rehabilitation intervention (Great Strides) for early RA was developed to address this, consisting of two compulsory sessions and up to four optional sessions delivered over three months. Physiotherapists and podiatrists received bespoke training to deliver Great Strides, incorporating motivational interviewing (MI) and behaviour change techniques (BCTs), to help patients to complete their walking exercises at home. The aim of this study was to assess fidelity of delivery within the Gait Rehabilitation in Early Arthritis Trial (GREAT) feasibility study. Methods: Four physiotherapists and two podiatrists delivered 78 Great Strides sessions across three centres in the UK. All sessions were audio recorded and double coded. The Motivational Interviewing Treatment Integrity (MITI) Rating Scale (scoring ≥4 represents good proficiency) and tailored treatment fidelity measures of the six core elements and 17 BCTs delivered in session 1, five core elements delivered in session 2, and 12 BCTs in session 2-6, were developed to examine fidelity of delivery. Two trained, independent assessors rated audio recordings of Great Strides and assessed the extent to which core elements, aspects of MI and BCTs were delivered across sessions. Results: Data from 28 (80%) adult participants across a total of 64 sessions were rated for core components and BCTs and 37 (50%) of sessions were analysed for MI. Relational (score=4.4) and technical (score=4.2) aspects of MI were delivered with good fidelity across the whole sample. The 6 core elements and 7 BCTs in Session 1 were conveyed with high (over 80%) treatment fidelity, but 10 further BCTs were not consistently delivered (range 23-69%). In session 2, the 5 core elements and 3 BCTs were provided with high fidelity, but another 9 BCTs were not reliably delivered (range 11-56%). Sessions 3 and 4 reliably delivered 3 out of 12 BCTs and only one session 5 and 6 was delivered. Inter-rater reliability showed agreement of over 80% was reached between raters for all sessions (range 82-87%). Conclusion: Physiotherapists and podiatrists were able to deliver the core elements of GREAT sessions with high fidelity and fidelity assessment methods were appropriate. Results showed a maximum of 4 sessions was sufficient. However, treatment fidelity might be enhanced with further training or greater on-going support, as findings suggested clinicians (physiotherapists) with previous MI experience were more proficient at offering key elements of MI. Additionally, the Great Strides intervention could be amended to improve delivery, as research shows complex interventions should consider mandatory BCTs alongside optional ones, depending on the needs of individual participants. Disclosures: E. Godfrey None. M. Sekhon None. G. Hendry None. N.E. Foster None. S. Hider None. M. van der Leeden None. H. Mason None. A. McConnachie None. I. McInnes None. A. Patience None. C. Sackley None. M. Steultjens None. A. Williams None. J. Woodburn None. L. Bearne None.